2009
DOI: 10.1128/aem.02897-08
|View full text |Cite
|
Sign up to set email alerts
|

FvtA Is the Receptor for the Siderophore Vanchrobactin inVibrio anguillarum: Utility as a Route of Entry for Vanchrobactin Analogues

Abstract: Some strains of Vibrio anguillarum, the causative agent of vibriosis in a variety of marine animals, produce a catechol-type siderophore named vanchrobactin. The biosynthetic pathway and regulation of vanchrobactin are quite well understood. However, aspects concerning its entry into the cell have remained uncharacterized. In the present study we characterized two genes, fvtA and orf13, encoding potential TonB-dependent ferricvanchrobactin receptors in serotype O2 V. anguillarum strain RV22. We found that an f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
1
38
0
2
Order By: Relevance
“…The catecholate-type siderophore Ent is utilized as the iron source by several Gram-negative bacteria, including V. cholerae (Mey et al, 2002), V. anguillarum (Balado et al, 2009;Naka & Crosa, 2012), Pseudomonas aeruginosa (Dean & Poole, 1993;Ghysels et al, 2005), Neisseria gonorrhoeae (Carson et al, 1999), Bordetella species (Beall & Sanden, 1995) and Campylobacter species (Palyada et al, 2004;Xu et al, 2010). In this study, we also showed that V. .…”
Section: Necessity Of Irgb and Vctr Together With Ent For Irga And Vcsupporting
confidence: 69%
See 2 more Smart Citations
“…The catecholate-type siderophore Ent is utilized as the iron source by several Gram-negative bacteria, including V. cholerae (Mey et al, 2002), V. anguillarum (Balado et al, 2009;Naka & Crosa, 2012), Pseudomonas aeruginosa (Dean & Poole, 1993;Ghysels et al, 2005), Neisseria gonorrhoeae (Carson et al, 1999), Bordetella species (Beall & Sanden, 1995) and Campylobacter species (Palyada et al, 2004;Xu et al, 2010). In this study, we also showed that V. .…”
Section: Necessity Of Irgb and Vctr Together With Ent For Irga And Vcsupporting
confidence: 69%
“…Three sets of TonB systems, termed TonB1, TonB2 and TonB3, are present in this bacterium (Kuehl & Crosa, 2010), and the energy required for PvuA1 and PvuA2 to transport ferric vibrioferrin is provided by the TonB2 system, and both the TonB1 and TonB2 systems, respectively (Tanabe et al, 2011). In addition, V. parahaemolyticus can utilize hydroxamate-type xenosiderophores such as desferri-ferrichrome and aerobactin (Funahashi et al, 2003(Funahashi et al, , 2009 et al, 1986;Balado et al, 2009;Griffiths et al, 1984) and a xenosiderophore enterobactin (Ent) mainly produced by members of the family Enterobacteriaceae (Carson et al, 1999; Mey et al, 2002;Naka & Crosa, 2012; Stork et al, 2004;Wyckoff et al, 2007). However, to our knowledge, the ability of V. parahaemolyticus to utilize catecholate-type xenosiderophores has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the genes were conserved throughout the strains; however, the anguibactin biosynthesis and transport genes were found only on the pJM1 plasmid in the 775 strain, although the RV22 strain had homologues of the fatABCD genes. These genes appeared not to be expressed (5,51). The tonB1 and tonB2-ttpC clusters were found in all of the V. anguillarum strains, but only the tonB1 system was identified in V. ordalii.…”
Section: Fig 3 Genomic Islands Of Strain 775 Predicted By Islandviementioning
confidence: 87%
“…V. cholerae transports vibriobactin via the outer membrane receptor ViuA (94). Similarly, PvuA is the vibrioferrin receptor in V. parahaemolyticus (97), VuuA is the vulnibactin receptor in V. vulnificus (98), and FvtA transports vanchrobactin in V. anguillarum (99). The siderophore receptors are typically localized to the outer membrane without the need for accessory factors.…”
Section: Transport Of Iron Complexesmentioning
confidence: 99%